2018
DOI: 10.1108/jima-01-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation into consumption of halal cosmetic products: the evidence from India

Abstract: Purpose India accounts for the third-largest Muslim population in the world after Indonesia and Pakistan. The previous studies about halal consumption have focused on the “food and money industry” only. Muslim consumers are prohibited from using alcohol, pork and other items in any form; the rising awareness among Muslims has led to the rapid growth in demand of halal cosmetic products around the globe. This paper aims to present a framework of halal consumers’ purchase and explores the factors that Indian con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 43 publications
5
92
1
7
Order By: Relevance
“…The halal labeling is a factor which becomes the consumers' decision in buying the beauty product. Consistent with the research (Anam et al, 2018;Shahid et al, 2018;Abd Rahman et al, 2015) found that the halal labeling has a significant correlation for the purchasing decision of the Islamic beauty product. It proves that the availability of the halal label on the cosmetics product has given a positive value which has a great opportunity in affecting the purchasing decision of the beauty product.…”
Section: The Halal Labeling Impact For the Purchasing Decision Of Thesupporting
confidence: 83%
See 2 more Smart Citations
“…The halal labeling is a factor which becomes the consumers' decision in buying the beauty product. Consistent with the research (Anam et al, 2018;Shahid et al, 2018;Abd Rahman et al, 2015) found that the halal labeling has a significant correlation for the purchasing decision of the Islamic beauty product. It proves that the availability of the halal label on the cosmetics product has given a positive value which has a great opportunity in affecting the purchasing decision of the beauty product.…”
Section: The Halal Labeling Impact For the Purchasing Decision Of Thesupporting
confidence: 83%
“…There is an positive and significant aspect namely competitive price, income, availability of the product and trusted halal certification. It is contrast with a research carried out by (Shahid et al, 2018;Abd Rahman et al, 2015) which found that the halal product selecting ignored the price and the income as the predictor variable.…”
Section: Influence Of Price For Purchasing Decision Of Halal Cosmeticcontrasting
confidence: 71%
See 1 more Smart Citation
“…The number of studies on modelling a firm's profitability has increased in recent years (e.g., Hirsch and Schiefer, 2016;Lee and Alnahedh, 2016;Hongwei et al, 2017;Islam and Khan, 2019). Some of them focused on cultural/religion-oriented markets from consumer perspective (Aisyah, 2017;Mustafar et al, 2018;Nawawi, Roslin and Hamid, 2018;Shahid, Ahmed and Hasan, 2018;Sriminarti and Nora, 2018;Putri, Daryanti and Ningtias, 2019). However, there is a paucity of research attempts modelling the profitability of halal markets from firm and industry perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Islam has detailed rules regarding consumption activities, which lead to the halal concept. Many studies of halal consumption activities have been carried out, but more studies discuss determinant factors in the consumption of halal products (Ali, Xiaoling, Sherwani, & Ali, 2017;Arsil, Tey, Brindal, Phua, & Liana, 2018;Asnawi, Sukoco, & Fanani, 2018;Ayyub, 2015;Omar, Zainol, Thye, Ahmad Nordin, & Nazri, 2017;Shahid, Ahmed, & Hasan, 2018). Very little research has been done that seeks to explore more deeply about the concept of halal in a practical manner in that it is more applicable to be utilized.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%